PHONETIC STYLISTIC DEVICES IN LITERATURE (TECHNICAL SCIENCE RESEARCH IN UZBEKISTAN, 2023)
In literature, writers often employ various stylistic devices to enhance the reader's experience. Alongside common tools such as metaphors, similes, and imagery, phonetic stylistic devices play a crucial role in creating a unique aesthetic and engaging the audience. These devices focus on the sounds and rhythms of words, showcasing the beauty and musicality of language. In this article, we will explore some of the key phonetic stylistic devices used in literature and their impact on the overall artistic expression.